Social media and recruitment: Examining (counter) productive diversity messages - Robyn Brouer; Rebecca Badawy; Michael Stefanone (Organization Management Journal (OMJ), 2022)
Purpose - This study aims to explore the consequences of inconsistent diversity-related signals for job seekers. Information sources include strategically crafted corporate signals and independent sources. The authors seek to understand the effect of inconsistent diversity signals on job seekers attitudes and behavior during recruitment. Design/methodology/approach - An experiment was conducted wherein two samples from jobseeking populations were first exposed to a fictitious corporate website and then to LinkedIn profiles of that organization's employees, with systematically varied diversity signals. Findings - Results demonstrated that conflicting diversity signals had negative effects on perceived organizational attractiveness in the student sample (N = 427) and on organizational agreeableness in the working sample (N = 243). Negative organizational attraction was related to a lower likelihood of participants applying. Practical implications - This work provides a stark but an important message to practitioners: signaling diversity-related values on corporate websites may backfire for organizations that actually lack diversity. Originality/value - Few studies have combined communication theories with recruitment to examine the link between diversity signals and inconsistent information gathered via social media.
Keywords: 650; Diversity; Social media; Recruitment; LinkedIn; Warranting